2008
DOI: 10.1007/s10792-007-9184-0
|View full text |Cite
|
Sign up to set email alerts
|

Primary orbital mesenchymal chondrosarcoma: a case report and literature review

Abstract: Although rare, MC should be considered in the differential diagnosis of a well-circumscribed orbital lesion in young adults, especially when CT scans reveal areas of calcification within the tumor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 14 publications
2
8
0
Order By: Relevance
“…8,9,14,20) Intraorbital MC is extremely rare, with only a few reported cases. [2][3][4][5][6][9][10][11][15][16][17][18][19][20][21][22][23] We describe a case of intraorbital MC successfully treated with intraorbital exenteration.…”
Section: Introductionmentioning
confidence: 99%
“…8,9,14,20) Intraorbital MC is extremely rare, with only a few reported cases. [2][3][4][5][6][9][10][11][15][16][17][18][19][20][21][22][23] We describe a case of intraorbital MC successfully treated with intraorbital exenteration.…”
Section: Introductionmentioning
confidence: 99%
“…Skin lesions may originate from a pre-existing contiguous lesion such as a neighboring mucosa, from the hematogenous dissemination of the fungus, or rarely, from the direct inoculation of P. brasiliensis into the skin [9]. As neither previous visible lesion nor history of local trauma was reported by our patient, we hypothesize that the eyelid lesion was from hematogenous dissemination, although no evident pulmonary infection was detected.…”
Section: Discussionmentioning
confidence: 67%
“…Approximately 43% of these lesions are ulcerated, 26% are infiltrative, 21% are papulous-nodal-tumoral, 7.3% vegetant or verrucous-vegetant, and 2% are abscessed lesions [9]. Belfort Jr. et al [10] reported the most common eyelid and conjunctival findings in PCM from their experience as: eyelid ulcerated lesions with hemorrhagic features that can involve lacrimal ducts, palpebral edema and hyperemia due to local tissue destruction, diffuse conjunctival hyperemia sometimes with purulent secretion due to secondary infection, and painless cervical, pre-auricular or submandibular lymphadenopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Orbital wall tumor is rare, but a variety of primary and secondary tumors involving the orbital wall have been reported [1,2]. Intradiploic meningioma is another rare tumor [3,4].…”
mentioning
confidence: 99%
“…The Tl SPECT findings in our patient were comparable to those of patients with benign meningioma showing high blood flow and low malignancy. Rapidly growing skull tumors, such as chondrosarcoma, sometimes occur in the orbital wall [1,2]. Chondrosarcoma is an aggressive tumor with a high tendency for recurrence and is capable of distant metastasis.…”
mentioning
confidence: 99%